Electromagnetic Field Enhancement of Nanostructured TiN Electrodes Probed with Surface-Enhanced Raman Spectroscopy - Oener, Ibrahim Halil; David, Christin; Querebillo, Christine Joy; Weidinger, Inez M.; Ly, Khoa Hoang (Sensors, 2022)
We present a facile approach for the determination of the electromagnetic field enhancement of nanostructured TiN electrodes. As model system, TiN with partially collapsed nanotube structure obtained from nitridation of TiO2 nanotube arrays was used. Using surface-enhanced Raman scattering (SERS) spectroscopy, the electromagnetic field enhancement factors (EFs) of the substrate across the optical region were determined. The non-surface binding SERS reporter group azidobenzene was chosen, for which contributions from the chemical enhancement effect can be minimized. Derived EFs correlated with the electronic absorption profile and reached 3.9 at 786 nm excitation. Near-field enhancement and far-field absorption simulated with rigorous coupled wave analysis showed good agreement with the experimental observations. The major optical activity of TiN was concluded to originate from collective localized plasmonic modes at ca. 700 nm arising from the specific nanostructure.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Electromagnetic field enhancement; Nanotubes; Plasmonics; Surface enhanced Raman scattering spectroscopy; Titanium nitride